2020
DOI: 10.3389/fcimb.2020.597408
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Metabolomic Analyses Provide Insights into the Mechanism on Arginine Metabolism Regulated by tRNA Modification Enzymes GidA and MnmE of Streptococcus suis

Abstract: GidA and MnmE, two important tRNA modification enzymes, are contributed to the addition of the carboxymethylaminomethyl (cmnm) group onto wobble uridine of tRNA. GidA-MnmE modification pathway is evolutionarily conserved among Bacteria and Eukarya, which is crucial in efficient and accurate protein translation. However, its function remains poorly elucidated in zoonotic Streptococcus suis (SS). Here, a gidA and mnmE double knock-out (DKO) strain was constructed to systematically decode regulatory characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…tRNA modification ensures efficient and accurate protein synthesis and promotes cellular health and growth ( Manickam et al, 2016 ). Glucose-inhibited division protein (GidA), which is highly conserved in prokaryotes, serves as a tRNA modification enzyme and catalyzes the addition of a carboxymethylaminomethyl (cmnm) group at the 5′ position of the wobble uridine (U34) of tRNAs ( Yu et al, 2019 ; Gao et al, 2020 ). GidA modification is evolutionarily conserved in bacteria and Eukarya, which is essential for efficient and accurate protein translation ( Fislage et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…tRNA modification ensures efficient and accurate protein synthesis and promotes cellular health and growth ( Manickam et al, 2016 ). Glucose-inhibited division protein (GidA), which is highly conserved in prokaryotes, serves as a tRNA modification enzyme and catalyzes the addition of a carboxymethylaminomethyl (cmnm) group at the 5′ position of the wobble uridine (U34) of tRNAs ( Yu et al, 2019 ; Gao et al, 2020 ). GidA modification is evolutionarily conserved in bacteria and Eukarya, which is essential for efficient and accurate protein translation ( Fislage et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that the central metabolism shifts from the glycolysis pathway toward the PPP in S. suis after glycogen induction ( Figure 3 ) and presents the possible stress responses of S. suis under glycogen-induced conditions. Moreover, the increased ADS ( Table 3 ) can catalyze the conversion of arginine to ornithine, thereby producing ammonia, carbon dioxide, and ATP, which provides energy and protection for S. suis during stress ( Gao et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a derived peptide of 3-oxoacyl-[acyl-carrier-protein] reductase responsible for the fatty acid biosynthesis was identified in SS2, SS14, SS7, and SS27. The previous studies demonstrated that this enzyme was associated with the fatty acid biosynthesis of virulent SS2 [ 27 , 28 ]. Thus, we could assume that this fatty acid biosynthesis-associated enzyme is significant for S. suis adaptation in the host-simulated environment.…”
Section: Discussionmentioning
confidence: 99%